2016
DOI: 10.21475/poj.160902.p7644x
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide analysis of heat shock transcription factor (HSF) family in chickpea and its comparison with Arabidopsis

Abstract: Plants cope with thermo-stress by increased expression of heat shock genes. These genes encode various heat shock proteins (HSPs) which rapidly accumulate and protect plants following hasty heat stress. Heat shock transcription factors (HSFs) primarily regulate expression of HSP genes by deciphering conserved binding motifs in promoter region. We retrieved HSF genes of Arabidopsis and chickpea from the online data bases and analyzed their structure and properties using bioinformatics tools. Here, we reported 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
(22 reference statements)
1
11
0
Order By: Relevance
“…In this study, response of heat shock protein to heat stress was greater than that to drought stress, and the greater heat shock protein was observed with exposure to the drought + heat stress. Heat shock proteins play vital role in abiotic stresses particularly under temperature stress 66 . Several studies regarding the effects of a combination of drought and heat stress on the heat shock protein of tobacco 11 , wheat 67 and Arabidopsis 53 have suggested that the effect of combined stresses on plants was different from that of heat or drought stress applied individually.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, response of heat shock protein to heat stress was greater than that to drought stress, and the greater heat shock protein was observed with exposure to the drought + heat stress. Heat shock proteins play vital role in abiotic stresses particularly under temperature stress 66 . Several studies regarding the effects of a combination of drought and heat stress on the heat shock protein of tobacco 11 , wheat 67 and Arabidopsis 53 have suggested that the effect of combined stresses on plants was different from that of heat or drought stress applied individually.…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock transcription factors (HSFs) constitute a large TF family with evident roles in growth, development and reproduction [36,42]. In addition, their important role in abiotic stress tolerance has emerged recently in several crop species [23,24,34,43]. HSFs are comprised of 25 members in rice and 22 members in Arabidopsis [28].…”
Section: Discussionmentioning
confidence: 99%
“…HSF transcription factors normally regulate the expression of various stress-responsive genes via binding to heat shock elements (HSEs) [23]. In silico cis-element analysis of the promoter of OsADC1 and AtADC1 showed that they contain HSE elements, so can be effectively bound by HSFs.…”
Section: Oshsfa3 Interacts With Osadc1 and Atadc1 Promotermentioning
confidence: 99%
See 2 more Smart Citations